Noise effect and parameter estimation in excitable dynamic media - Guzzi, Rodolfo (Organisms. Journal of Biological Sciences, 2019)
Stochasticity in gene expression arises from fluctuations in transcription and translation. This phenomenon has implications for cellular regulation. The novel techniques for single-cell analysis have provided new experimental and theoretical investigations. As a result, a coherent picture of stochasticity in prokaryotic and eukaryotic gene expression has been obtained. In this paper, we analyze the behavior of a stochastic process applied to Brusselator, investigating the noise affecting this system. Once the noise has been retrieved, the maximum likelihood estimation may be used to retrieve the parameters of the system itself. Although these techniques have been applied to simple reaction processes as those hypothesized with Brusselator, the methodology is general and can be used to any reaction and related linear and nonlinear ODEs.